Coal Permeability Variation during the Heating Process considering Thermal Expansion and Desorption Shrinkage. (10th March 2022) - Su, Xiaoyu; Feng, Zengchao; Cai, Tingting; Shen, Yongxing
Abstract : In order to explore the influence of coal deformation caused by temperature and desorption on seepage characteristics in the process of heat injection mining of coalbed methane, the permeability test, thermal expansion, and constant temperature adsorption desorption of coal samples under different temperature and stress states were carried out using the high temperature multifunctional triaxial test system, and the influence of thermal expansion and desorption deformation effect on coal permeability in the process of temperature increase is studied. The results show that (1) with the increase of temperature, the sensitivity of coal thermal expansion deformation to temperature decreases gradually. The thermal expansion deformation makes the coal matrix expand, and the seepage channel is squeezed and the permeability decreases. (2) The effect of thermal expansion deformation is related to the porosity of coal. When the porosity of coal is high, the thermal expansion deformation reduces the permeability; on the contrary, the inward expansion of thermal expansion deformation is limited, and the effect on permeability is weakened. (3) The desorption of coal cause matrix shrinkage. The higher the desorption amount, the more obvious the shrinkage and the higher the permeability. Increasing temperature promotes desorption deformation of coal and increases permeability. (4) In the process of increasing temperature, the change of coal permeability is affected by thermal expansion deformation and desorption deformation. With the increase of temperature, when the influence of thermal expansion deformation on coal permeability is dominant, the permeability decreases gradually, and when desorption deformation is dominant on coal permeability, the permeability increases gradually. (5) With the increase of axial pressure, confining pressure, and pore pressure, the decrease of coal porosity is smaller. When the temperature increases, the temperature corresponding to the minimum permeability point is smaller. The research conclusion provides a basis for the technology of heat injection mining coalbed methane.